A global overview of guided endodontics: a bibliometric analysis - Lima, Thaine Oliveira (2024)
Introduction: This review aimed to analyze the trend and main characteristics of articles related to guided endodontics (GE). Methods: The search was conducted in May 2023 on Web of Science. GE-related articles were included, and conferences were excluded. Three researchers selected the articles and extracted: the number of citations; year and journal; design and study theme; authorship and institutions; country and continent. Collaborative networks were generated in the Visualization of Similarities Viewer software. The relationship between data was determined by Spearman\'s correlation. Google Trends was used to investigate the global popularity of GE research. Results: The search resulted in 135 articles, of which 85 were included. The most cited article totaled 116 citations. The studies were published between 2016 and 2023, most frequently in 2022 (n = 22). The most prevalent journal was the Journal of Endodontics (n = 28). Case report (n = 38) was the most frequent study design. The most studied theme was the use of static GE for calcified canals (n = 27). Connert T was the author with the highest number of articles (n = 13). The University of Basel (n = 9) stood out. The most prevalent country was Brazil (n = 13). Europe was the most frequent continent (n = 38). Visualization of Similarities Viewer demonstrated an interaction between authors. There was a moderate positive correlation between citations and the impact factor (rho = .483). According to Google Trends, the United States was the country that most researched GE. Conclusions: Based on this review, a more significant research interest in GE was observed in Europe, addressing the application of GE in locating severely calcified root canals.